Characterization and magnetic properties study for magnetite nanoparticles obtained by pulsed laser ablation in water - Svetlichnyi, Valerii A.; Shabalina, Anastasiia V.; Lapin, Ivan N.; Goncharova, Darya A.; Velikanov, Dmitry A.; Sokolov, Alexey E. (Applied physics A: Materials science and processing)
Magnetite (Fe3O4) nanoparticles of 1-10 nm (with the maximum at 2 nm) were obtained via pulsed laser ablation of iron target in water in form of a stable dispersion without addition of surfactants and stabilizers. The structure of the material obtained was investigated using transmission electron microscopy, scanning electron microscopy, and Brunauer-Emmett-Teller methods. To investigate the composition of the particles in the sample, such methods as Fourier transform infrared spectroscopy, Raman spectroscopy, differential scanning calorimetry, and X-ray diffraction, were applied. Magnetite phase was found to be sufficiently pure, it was not contaminated by other iron oxide phases and contained not more than 0.5% of metallic iron in form of large particles. The study of the magnetic properties of the magnetite nanoparticles obtained has shown that they exhibit ferrimagnetic behavior at room temperature with the paramagnetic contribution explained by the presence of fine superparamagnetic particles. © 2017, Springer-Verlag GmbH Germany, part of Springer Nature.